Associations of green space visitation patterns with sociodemographics, health, and perceptions: A cluster analysis using smartphone Wi-Fi and GPS data - Hwangseon Park; Kwangjune Choi; Changjun Lee; Hayoung Oh (PLoS ONE, 2025)
Understanding the multiple impacts of green spaces on individual health and overall quality of life is a key factor in urban planning and public health promotion. This study integrated smartphone Wi-Fi and GPS location data, survey data, and green space data to analyze the relationships between green space visitation patterns and sociodemographic characteristics, health, and green space perceptions of 1,715 residents of the Seoul metropolitan area in South Korea. Green space visitation patterns of urban residents were categorized into Non-Visitors (rarely visited green spaces), Weekday Visitors (weekday visits), Weekend Visitors (weekend visits), and Frequent Visitors (weekday and weekend visits). The health status of residents in each group was assessed using the EQ-5D-5L scale, which evaluates overall mental and physical health. The analysis indicated variations in educational background across groups, with the Non-Visitors and Frequent Visitors showing differing distributions. In addition, the Weekend Visitors group had the best mental and physical health, which were significantly different from the Non-Visitors group. Perceptions of green space were significantly more positive for Weekend Visitors and Frequent Visitors than for Non-Visitors. These results suggest that green space usage patterns can be segmented not only by frequency of visits, but also by when and whether they are visited. It is also worth noting the differences in green space visitation by educational background, highlighting the need for environmental education programs and campaigns to mitigate these environmental inequalities. The positive effect of weekend visits, in particular, highlights the value of green spaces for leisure and relaxation. This finding suggests that urban planning can benefit city residents by providing high-quality, easily accessible green spaces.